Reptiles - Das, I.; Pui, Yong Min; Shabrani, Adi; Karin, B.R; Breuer, H. (UNIMAS Publisher, 2016)
A total of 86 species of reptiles are now known from Gunung Penrissen. The earliest account in 1900 (based on his collections in 1899) by William Shelford included 24 species. As with the amphibian fauna, faunal turnover with elevation is distinct, with the lowlands inhabited by generalised Bornean lowland reptiles, the upper (> 1,200 m above sea level) elevations showing several Bornean endemics, including a few only otherwise known from Gunung Kinabalu, in northern Borneo.